2006
DOI: 10.1186/cc5046
|View full text |Cite
|
Sign up to set email alerts
|

Serum neuron-specific enolase as early predictor of outcome after in-hospital cardiac arrest: a cohort study

Abstract: Introduction Outcome after cardiac arrest is mostly determined by the degree of hypoxic brain damage. Patients recovering from cardiopulmonary resuscitation are at great risk of subsequent death or severe neurological damage, including persistent vegetative state. The early definition of prognosis for these patients has ethical and economic implications. The main purpose of this study was to investigate the prognostic value of serum neuron-specific enolase (NSE) in predicting outcomes in patients early after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…However, detection of NSE could be useful if measured after 24-48 h of TBI [67, 68]. Other study has found that elevated levels of NSE can be detected at an earlier time, and could be used as a prognostic marker [69]. In that study, NSE levels were measured at any time between 12 and 36 h, and the authors were able to detect NSE levels as a marker of prognosis after cardiac arrest.…”
Section: Nse In Other Acute Injuries To Cnsmentioning
confidence: 96%
“…However, detection of NSE could be useful if measured after 24-48 h of TBI [67, 68]. Other study has found that elevated levels of NSE can be detected at an earlier time, and could be used as a prognostic marker [69]. In that study, NSE levels were measured at any time between 12 and 36 h, and the authors were able to detect NSE levels as a marker of prognosis after cardiac arrest.…”
Section: Nse In Other Acute Injuries To Cnsmentioning
confidence: 96%
“…Comparing of the result with non infectious disease outcome, serum levels of NSE in first few days of ischemic stroke can serve as a useful marker to predict stroke severity and early functional outcome20). Study by Rech et al21) demonstrates that NSE levels measured early in the course of ischemic cerebral injury are significantly higher in patients with unfavorable outcome than in patients with favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 This 40–62% “noise” is likely due to intra-individual differences in CSF clearance, affected by cardiac output, 33 sleep, 34 physical activity and aging, 3536 as well as systemic clearance and hepatic metabolism of soluble biomarkers. While this level of accuracy may be sufficient for some indications, such as providing prognostic value of recovery from CNS injury, 37 introducing 40–62% noise in pharmacodynamic outcomes in drug development or precision medicine applications may not be acceptable. At any rate, development of sensitive serum/plasma assays for CNS-specific biomarkers is welcomed, but the clinical utility of these assays needs to be evaluated against CSF assays, so that the sensitivity, specificity and correlations of these measurements to clinical outcomes are well understood.…”
Section: Biomarkersmentioning
confidence: 99%